MINERAL BUKAN LOGAM) DI KECAMATAN KUNTO DARUSSALAM TAHUN 2010-2013 - Maykel "; Erman " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research study Entitle political economy of mining management "base" (non-metal mineral mines) in the district Kunto Darussalam 2010-2013. This study aims to determine the cause of the lack of regulation of the mining base in the district rokan upstream by analyzing the existence of rent seeking practices that occur in the management of mining base in the district Kunto Darussalam. Rent seeking theory is a theory that became the foundation of thought in this study, in addition to the concept of shadow state is also used to describe forms of rent seeking practice and its impact in the management of mining base in the district Kunto Darussalam. The object of this research is the management of mining base in the district Kunto Darussalam conducted by the local government district rokan upstream. Rent seeking practices in the management of mining base in doing the mining and energy department officials rokan upstream counties with mine operators and officials of financial services and asset managers rokan district upstream with the contractor base in the determination of the tax base. Rent seeking practice is giving birth to their shadow state in the body upstream rokan local government district that makes the local regulations regarding the management of mining in the district upstream rokan not realized.Keywords : Base, Mining, Political Economy, Rent Seeking, Shadow State.